PEMODELAN TIME-LAPSE MICROGRAVITY UNTUK ESTIMASI PERUBAHAN MUKA AIRTANAH DI BANDUNG, JAWA BARAT - Wahyudi, Eko Januari; A. Kadir, Wawan Gunawan; Alawiyah, Susanti; Setianingsih, Setianingsih; Gunawan, Indra; Abdurrahman, Dadi (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2023)
Studies related to groundwater monitoring using geophysical methods have been carried out since the 1990s. Surface gavity data with a scheme of relative gravimeter measurements is chosen for monitoring in urban areas because it is quite fast, easy, affordable, and relatively low-impact on the environment. The significance of the time-lapse microgravity method for the target of this study depends on changes in the mass of water in the aquifer layer below the surface. The research area in this study covers the city of Bandung and several surrounding areas with an interpolated grid coverage of (18 x 17) km2. Gravity changes were determined by six repeated surveys at the same observation points from 2010 to 2021. The aim of this research is to develop a method for estimating groundwater table changes based on time-lapse microgravity data modeling. The complexity of subsurface density changes is simplified for two parts related to near surface density changes and density changes in the intermediate aquifer layer. The trend of groundwater table data in 2010 is used as a reference to determine estimates for 2015, 2016 (February and August), 2019, and 2021. Modeling results for intermediate aquifers (confined groundwater system) provide changes in groundwater levels from 2010 with estimates reached ±23 meters, while the results of modeling at near surface (shallow groundwater level) indicate a groundwater level change of approximately ±8 meters from the year 2010.Keywords: microgravity, groundwater, modeling, hydrology, aquifer.